2018
DOI: 10.3390/molecules23092280
|View full text |Cite
|
Sign up to set email alerts
|

Application of Organo-Magadiites for the Removal of Eosin Dye from Aqueous Solutions: Thermal Treatment and Regeneration

Abstract: Na-magadiite exchanged with cetyl-trimethylammonium cations provided organophilic silicate materials that allowed for the effective removal of the acidic dye “eosin”. The organic cations were intercalated into the interlayer spacing of the layered silicate via an exchange reaction between the organic cations from their bromide salt and the solid Na-magadiite at room temperature. Different techniques were used to characterize the effect of the initial concentration of the surfactant on the structure of the orga… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 70 publications
6
13
0
Order By: Relevance
“…This part indicated that the modification of the PG clay with surfactants has enhanced the removal of an acidic dye. Similar data were obtained using different organo-silicates [ 25 , 63 ].…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…This part indicated that the modification of the PG clay with surfactants has enhanced the removal of an acidic dye. Similar data were obtained using different organo-silicates [ 25 , 63 ].…”
Section: Resultssupporting
confidence: 80%
“…As the C16TMA content increased, the removal amount was also improved due to the complete covering of the negative charge on PG clay by the surfactant, which means the electrical repulsion overcame [ 66 , 67 , 68 ]. Similar data were achieved using local clay mineral [ 32 ] and other silicate layered materials [ 25 , 63 ].…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…A number of regeneration methods were summarized and discussed in recent reviews [23,75]. In this study, a regeneration method was adopted with an efficient, eco-friendly, and easy to operate process, to reuse the spent waste bricks [19,76]. The treatment of fresh spent waste bricks was done after the first removal of basic blue 41 by a solution containing cobalt cations and an oxidant oxone.…”
Section: Regeneration Propertiesmentioning
confidence: 99%
“…There are so many hydrated sodium ions between the plates that the cationexchange capacity (CEC) is higher than other silicates, such as montmorillonite and can reach up to 2.22 meq/g [8], which was determined from the ideal formulation of MAG (Na2Si14O29). So far, the cation-exchange properties of MAG investigated [9][10][11][12][13], indicate that MAG can be used as an adsorbent, based on cation exchange [14,15]. According to the current study, MAG can be synthesized [16][17][18][19][20][21]; the laminate of MAG was composed of SiO4 and has no other impurities.…”
Section: Introductionmentioning
confidence: 91%